A filmic montage : revisiting Jeanneret’s voyage d’orient - Duarte, João Miguel Couto, 1966- (2021)
Le Corbusier (1887–1965) had already explored, at an earlier stage in his career, the possibility of capturing architecture and the world through the filmic medium. One could argue that the relationship Le Corbusier had with film developed when he was a young man, when he was still Charles-Édouard Jeanneret, which would make an assessment of the importance of his 1911 voyage d’Orient meaningful. To a large extent the genesis of the complex relationship Le Corbusier was to establish later with architecture and with the world can be traced back to those travels; indeed, they should be seen as the very roots of his identity. This paper sets out to understand the principles that may have nurtured Le Corbusier’s future relationship with film. His like-mindedness with Sergei Eisenstein (1898–1948) and the acknowledgement by both of the cinematographic qualities of the Acropolis in Athens, justify the attention that subsequent thought has given to the series of drawings Jeanneret produced of the monument. But other drawings by him should also be mentioned in this context, particularly the one he made of a house in Istanbul. The movement that is perceived between each of the drawings of the Acropolis is counterposed by the movement that exists in the interior of this drawing, which presents architecture as if observed by a gaze that moves through time, discerning in it a filmic montage that pre-announces his future approximation to architecture.